Unraveling the neuroimmune mechanisms in cancer-induced bone pain: New horizons for therapeutic intervention of the two-phase paradigm - Changming Wang; Haiwang Ji; Hanwen Wang; Ziyun Chen; Lan Zhou; Yan Yang; Yucui Jiang; Guang Yu; Ling Jiang; Zongxiang Tang (Proceedings of the National Academy of Sciences, 2025)
Cancer-induced bone pain (CIBP) is a severely painful condition that profoundly impacts patients’ quality of life. However, the neuroimmune mechanisms underlying CIBP remain largely elusive. Substance P (SP), which is known to play a pivotal role in pain perception, became the focal point of our study. To this end, we adopted a comprehensive approach combining behavioral and physiological methods to investigate its role in neuroimmune interactions in CIBP. The results showed that SP released by dorsal root ganglion (DRG) neurons via exocytosis initiates CIBP, with its release peaking on the 14th day and correlating with pain behavior. Macrophages were found to infiltrate the DRGs and the sciatic nerves. Notably, in mice with CIBP, the population of macrophage type I was significantly augmented. Significantly, we found that the deletion of macrophages led to a notable alleviation of CIBP, while the blockade of the SP-neurokinin 1 receptor pathway effectively mitigated the infiltration of macrophages and alleviated CIBP. In the advanced phase, DRGs released C-C Motif Chemokine Ligand 3 and C-C Motif Chemokine Ligand 2 to recruit macrophages. A two-phase model for CIBP progression in mice was proposed, with SP-induced macrophage infiltration in the primary phase and chemokine-mediated macrophage recruitment in the advanced phase. Our investigation has unearthed a previously unrecognized mechanism governing the neuroimmune interaction in CIBP, which highlights a critical target for impeding the progression of this debilitating pain, potentially opening up broad avenues for the development of effective therapeutic interventions at different stages of CIBP with cancer development.